Literature Review : Pengaruh Penggunaan Media Leaflet dan Video Audiovisual Terhadap Pengetahuan Sayur dan Buah Anak Sekolah Dasar - Mahmudah, Dini; Kurniasari, Ratih (Peneliti.net, 2024)
Nutrition education is needed to find out what foods are consumed by children for physical growth and cognitive development. In addition, to get used to consuming nutritious food, because eating habits from childhood will continue until adolescence to adulthood. This study aims to determine the effect of leaflet and video media on knowledge of fruit and vegetable consumption in elementary school children. This study used an extension method with leaflet and video media and a pre-post test was conducted on knowledge of fruit and vegetable consumption in elementary school children. The subjects of this research were taken by random sampling technique through questionnaires totaling 20 respondents, including grades 4-5 of elementary schools. Based on the findings of this research, it can be concluded that there is a genuine or substantial difference or effect associated with awareness of vegetable and fruit eating.